EFFECT OF BODY MASS INDEX ON LENGTH OF ICU STAY AFTER OPEN HEART SURGERY (The Research of Medical Science Review, 2025)
Background: Body Mass Index (BMI) has been strongly linked with health risk that can affected the post-operative outcomes of treatment and the increase the stay time of intensive care unit (ICU) after open heart surgery Objective: Investigate the relations between the BMI categories (underweight,normal, overweight, and obese) and the length of ICU stay with respect to recovery trajectories, resource utilization, and the obesity paradox. Methodology: The study is a longitudinal one taking a retrospective view from 2019 until 2024 on about 350 individuals undergoing open-heart surgery. They were classified according to their BMI into four groups. The statistical analysis employed ANOVA, regression, and Kaplan-Meier survival curves. Results: Obesity is associated with a longer ICU stay (mean: 4.1 days) than other BMI groups with complications such as infection, long ventilation, and so The paradox about obesity shows those mild cases would increase their long-term survival. Conclusion: The recovery from the ICU is significantly affected by the BMI of an individual. It is important to adopt perioperative strategies with regard to the individual BMI-centric risks if care optimization improving recovery trajectories among patients.